ANALISIS KAJIAN SOSIAL EKONOMI PEMBANGUNAN DAN PERLUASAN TOSERBA “ X ” - Desfitriady, Desfitriady; Kusmayadi, Tatang (2018)
The purpose of this study is to know and understand the community in the Village Sayati Margahayu District Bandung regency with the development and extension of department store (Convenience Store)